مواقف أعلام سوف من القضية الفلسطينية - سليم مكاوي; إبراهيم مكاوي (جامعة الوادي - University of Eloued, 2025)
تهدف هذه الدراسة الموسومة بمواقف اعلام سوف من القضية الفلسطينية موقف مجموعة من الشخصيات العلمية والفكرية والدينية المنتمية الى منطقة وادي سوف بالجزائر، خلال القرن العشرين من القضية الفلسطينية ،باعتبارها إحدى القضايا المركزية في الوجدان العربي والإسلامي وقد سعت الدراسة الى إبراز طبيعة هذه المواقف ، والوسائل التي عبر من خلالها هؤلاء الأعلام عن تضامنهم مع فلسطين ، سواء عبر الكتابة التاريخية أو الشعر أو الصحافة أو النشاط الديني والتربوي وقد شملت الدراسة كلا من : أبو القاسم سعد الله ، الأمين العمودي ، محمد العيد آل خليفة ،حمزة شنوف والعروسي حويتي ، بوصفهم نماذج بارزة لالتقاء الوعي الوطني بالفكر القومي والإسلامي في الدفاع عن فلسطين ، إعتمدت الدراسة على المنهج التاريخي التحليلي ، من خلال تتبع سير هؤلاء الأعلام وتحليل مواقفهم في ضوء الظروف السياسية والفكرية التي عاشوها. مستندة الى مصادر متنوعة مثل كتب التراجم والدواوين الشعرية والمقالات الصحفية والمذكرات الشخصية . توصلت الدراسة الى ان مواقف أعلام سوف من القضية الفلسطينية لم تكن سطحية أو آنية بل نابعة من قناعة فكرية عميقة بوحدة القضايا العربية ، ومن إرتباط وجداني وديني بفلسطين ، ما يجعلهم جزءا من المشروع الثقافي المقاوم في الجزائر والعالم الإسلامي . "this study,entitled the stances of souf figures on the palestinian cause, explores the positions of a group of scholary , intellectual, and religious figures from the souf region in algeria during the 20th centuryregarding the palestinian issu a central cincern in both arab and islamic consciousness. the study aims to highlight the nature of their engagement with the cause and the means through which they expressed solidarity with palestine, whether through historical writing, poetry, gournalism, or religious and educational activities. the figures examined include , abu al casim saadallah, muhammad al aid al khalifa, mohammad al amin al amoudi, hamza chennouf, and al aroussi howaiti , who represent a convergense of national awareness with arab and islamic thought in the defense of pakestine. the study adopts a historical analytical approach , tracing the biographies of these figures and analyzing their positions in light of the political and intellectual contexts they experienced. it draws upon a wide range of sources including biographical works, poetry collection, press articles , and personal memoirs. the study concludes that the stances of soufs figures toward the palestinian cause were not superficial or mommentary , but rather stemmed from a deep inellectual conviction in the unity of arab causes and a strong spiritual and emotional connection to palestine . this makes them part of the broader cultural and intellectual resitance movement in algeria and the islamic world."
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي الحديث والمعاصر
Keywords: العروسي حويتي; حمزة شنوف; محمدحمد الأمين العمودي; محمد العيد آل خليفة; أبو القسم سعد الله; القضية الفلسطينية; palestinian cause abu al kasim saadallah; muhammad al aid al khalifa; muhammad al amin al amoudi; hamza chennouf; al aroussi howaity.